The Dynamics of Interpersonal Communication Between Teachers and Students in Individual Counseling Services at Public Elementary School 2 Wlahar Purbalingga - Siwi Tami Wuryanti; Usri Maharyati; Siti Nurjanah (Journal of Educational Sciences, 2026)
The dynamics of interpersonal communication between teachers and students in individual guidance services at the elementary school level play an important role in supporting the effectiveness of guidance activities. This study employed a descriptive qualitative approach to describe the process of interpersonal communication between teachers and students at SD Negeri 2 Wlahar Purbalingga. Data were collected through observation, in-depth interviews, and documentation. The findings revealed that interpersonal communication in individual guidance services occurred in a two-way and dynamic manner. Teachers not only provided guidance and direction but also acted as listeners and facilitators who gave students opportunities to express their feelings and personal problems. The quality of interpersonal communication was influenced by teachers’ empathy, active listening skills, the use of simple and understandable language, students’ trust, and a comfortable, non-judgmental communication atmosphere. The study also identified several obstacles, including limited time, teachers’ workload, lack of private counseling spaces, and students’ low confidence in expressing themselves openly. The findings indicate that effective interpersonal communication can enhance students’ openness and support the success of individual guidance services in elementary schools.